Petrogenesis of the metacarbonate and related rocks of the silgará formation, central santander massif, colombian andes: an overview of a “reaction calcic exoscarn” (2008)
Metacarbonate rocks (pure and impure marbles, carbonate-silicate rocks, calc-silicate rocks and carbonate-bearing silicate rocks) form a very complex group within the metamorphic sequence of the Silgará Formation at the central Santander Massif (CSM). These rocks are interpreted as derived from a sedimentary sequence (including limestones and dolostones, carbonate-bearing mudstones,  sandstones, tuffaceous and evaporitic sediments and marlstones) overprinted by near-isochemical regional metamorphism. They usually appear as scarce intercalations from millimeter up to meter scale, within the high-grade pelitic rocks, in the lower part of the metamorphic section, although the proportion of metacarbonate rocks can be higher and different marble layers are exploited. We report for the first time the occurrence of a "reaction calcic exoskarn", which corresponds tosuch metacarbonate rocks, taking into account that a skarn can be developed during regional metamorphism and by different metasomatic processes, adjacent to intrusive bodies, along faults and shear zones, and what defines these rocks as a skarn is its mineralogy, which includes a variety of calc-silicate and associated minerals, usually dominated by garnet and pyroxene. Therefore, this paper focus attention to the occurrence of metacarbonate andrelated rocks, which occurs as small scale reactions zones that show a gradational contact from garnet-bearing pelitic rocks to marbles or carbonate-silicate rocks, giving particular interest to the calc-silicate rocks, which are characterized by the presence of elongated grains of banded clinopyroxene (diopside) and scapolite and massiveor scattered garnet. Several reaction-zones occur in the contact between impure calcite marble and garnet-bearing metapelite and the sequence of mineral assemblages in these reaction zones is: biotite + plagioclase K-feldspar garnet (Zone I), biotite + plagioclase K-feldspar garnet staurolite epidote (Zone II),plagioclase + amphibole garnet epidote (Zone III), amphibole + diopside + garnet + plagioclase (Zone IV), plagioclase + diopside scapolite (Zone V), epidote calcite (Zone VI), and calcite dolomite (Zone VII).